(untitled) (Baghdad Science Journal, 2007)
The antibacterial effect of (Eruca sativa) extract was evaluated by an in vitro study testing the growth of various Gram-Positive and Gram-Negative bacteria . The bactericidal activity of this extract was analyzed by serial dilution in tubes. This study,found that Gram-Negative and Gram-Positive bacteria susceptible to very low eruca concentrations. On the other hand, Gram-positive bacteria were more susceptible than Gram-negative bacteria, the minimal bactericidal concentration of Gram-positive bacteria was 5 mg ml-1 but minimal bactericidal concentration of Gram-negative bacteria was 10 mg ml-1 that mean duble inhibation concentration of Gram-positive bacteria . this study suggest that Eruca sativa leaves have inhibation effect on Gram-Posative and Gram-Negative bacteria and Eruca sativa was natural material with little side effect.